(untitled) (Sport and Exercise Psychology, 2025)
This article integrates the main findings from the scientific literature on sensation seeking in winter sports, with particular attention to snowboarding. It examines the role of the sensation seeking personality trait in modulating risk-taking behavior and its relationship with helmet use, in order to understand whether wearing a helmet increases risk or whether psychological factors are the primary drivers of such behaviors. Furthermore, the paper explores the characteristics of extreme sports, the psychological profiles of athletes, and the role of the sport psychologist in providing support and prevention.